Drivers of existing and emerging food safety risks: Expert opinion regarding multiple impacts. (August 2018) - Kendall, Helen; Kaptan, Gulbanu; Stewart, Gavin; Grainger, Matthew; Kuznesof, Sharron; Naughton, Paul; Clark, Beth; Hubbard, Carmen; Raley, Marian; Marvin, Hans J.P.; Frewer, Lynn J.
Abstract: Considerable research effort is invested in the development of evidence to help policy makers and industry deal with the challenges associated with existing and emerging food safety threats. This research aimed to elicit expert views regarding the relationship between the drivers of existing and emerging food safety risks, in order to facilitate their control and mitigation, and to provide the basis for further international policy integration. A Delphi approach involving repeated polling of n = 106 global food safety experts was adopted. The primary drivers of existing and emerging food safety risks were identified to be demographic change, economic driving forces, resource shortages, environmental driving forces, increased complexity of the food supply chain, water security and malevolent activities . The identification of socio-economic and biophysical drivers emphasises the need for a transdisciplinary and systems approach to food safety management and mitigation. The mitigation of hazards on a case-by-case basis is unlikely to have a major impact on food safety hazards but may have unintended effects (where positive or negative) across a broad spectrum of food safety issues. Rather a holistic or systems approach is required which can address both the intended and unintended effects of different drivers and their interactions. Highlights: Expert elicitation via Delphi of the drivers of existing and emerging food safety risks. Single drivers had multiple impacts upon food safety risks. Involving a range of stakeholders in the policy development process is important. A holistic or systems approach to the mitigation of food safety risks is required.